Co-developing digital inclusion policy and programming with indigenous partners: Interventions from Canada - Rob McMahon (Internet Policy Review, 2020)
Diverse rural Indigenous communities in Canada, like those in many regions of the world, are facing a variety of challenges and opportunities associated with the development, deployment, and adoption of rapidly emerging digital technologies. These include supply-side challenges (such as availability and cost) and demand-side challenges (such as appropriate digital literacy programmes). This article discusses two examples of digital inclusion co-developed with Indigenous peoples in Canada: a supply-side intervention focused on digital access policy, and a demand-side intervention focused on digital adoption.
Keywords: 300; Indigenous peoples; Community informatics; Digital policy; Digital literacy